Comparison of estimators of the mean radar reflectivity from a finite number of correlated samples - Fjortoft, R.; Lopes, A. (1999 IEEE International Geoscience and Remote Sensing Symposium, 1999)
The authors compare estimators of the mean radar reflectivity on images with different spectral properties. By working on complex data rather than detected images, they can take the speckle correlation into account and thus obtain more accurate estimates. A computationally efficient approximation of the optimal estimator is proposed.